2023
DOI: 10.7759/cureus.36773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual and Automated Nucleic Acid (RNA) Extraction Methods for the Detection of SARS-CoV-2 by qRT-PCR

Abstract: During the COVID-19 pandemic, several laboratories used different RNA extraction methods based on the resources available. Hence this study was done to compare the Ct values in qRT-PCR, time taken (sample processing-loading to PCR), manpower requirement, and cost of consumables between manual and automated methods. Materials and methodsA cross-sectional study was done on 120 nasopharyngeal/oropharyngeal swabs received in VRDL for RT-PCR testing. Based on the results of automated RNA extraction (Genetix, HT 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the study conducted by Kumar et al, 13 comparing two automated platforms with manual RNA extraction, found comparable efficacy in RNA extraction between the manual method and one of the automated methods. This consistency across studies supports the idea that various RNA extraction methods may yield different Ct values, yet the ultimate interpretation of results remains unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study conducted by Kumar et al, 13 comparing two automated platforms with manual RNA extraction, found comparable efficacy in RNA extraction between the manual method and one of the automated methods. This consistency across studies supports the idea that various RNA extraction methods may yield different Ct values, yet the ultimate interpretation of results remains unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic beads-based technology has been widely used in biomedical research [33][34][35][36][37], and has become one of the most used methods to extract viral RNA for screening for SARS-CoV-2 [36], as rapid diagnosis of COVID-19 is essential to restrict its spreading. A same extraction method combined with an automated approach, which is rapid, high-throughput, uniform and bears low cross contamination risk [50][51][52] may be employed for honey bee research, in particular for virus screening surveys to screen multiple colonies in a limited timeframe.…”
Section: Introductionmentioning
confidence: 99%
“…Automated nucleic acid extraction instruments have the potential to improve workflow and reduce variability in clinical laboratories. Some reports have already identified the value of automated nucleic acid extraction instruments compared to manual methods [23][24][25][26]. Although most reports mention the benefits of streamlining workflows and reducing hands-on time, the quality of extracted nucleic acids can vary.…”
Section: Introductionmentioning
confidence: 99%